Strategi Perbaikan Kualitas Biosolar Berdasarkan Kandungan Air dan TAN yang Meningkat Akibat Penyimpanan di Ruang Terbuka - Zakia Salsabillah; Muhamaad Arya Rizki; Alinanda Hendrasti; Joy Triadi Pangestu (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This study conducted a trial of B-30 products stored in miniature storage tanks outdoors to produce B-30 offspec products. Tests were also carried out on offspec B-30 products blended with new biosolar products. The research focused on the analysis of water content and Total Acid Number (TAN) using tools and materials that have been determined. The test results showed that biosolar products stored for two weeks in open space had an increase in moisture content and TAN value. An increase in water content is due to condensation during prolonged storage, while an increase in the TAN value indicates damage to the product. The addition of new biosolar in biosolar offspec aims to improve the quality of BioSolar damaged by storage. This study is relevant to understand the impact of storage on biosolar quality and improvement strategies that can be done.